New host and locality record for the parasitic isopod Ceratothoa carinata (Bianconi, 1869) (Crustacea: Isopoda: Cymothoidae), with molecular insights into its phylogeography - Salari, Mohammad; Khalaji-Pirbalouty, Valiallah; Ranjbar, Mohammad Sharif; Shahdadi, Adnan (Zootaxa, 2025)
A male and two females of the cymothoid isopod Ceratothoa carinata (Bianconi, 1869) were found in the buccal cavity of the Talang queenfish, Scomberoides commersonnianus Lacepède, 1801, representing a new host record. This parasitic isopod is widely distributed across the Indo-West Pacific, with its type locality in Mozambique. However, this is the first record of the species from the Gulf of Oman. Morphologically, our specimens closely match the diagnosis of the neotype. As there has been no previous record or description of the male for this species, the male characteristics are briefly described herein. In addition to morphological comparisons, we obtained two COX1 sequences and constructed a phylogeny using available Ceratothoa sequences from GenBank. In the phylogenetic trees, specimens of C. carinata from Japan, the Philippines, and the Gulf of Oman formed a monophyletic group within a well-supported clade. The mean genetic distances between C. carinata and other Ceratothoa species ranged from 17% to 31.5%, significantly exceeding the maximum genetic distance of 2.7% within C. carinata. Thirteen haplotypes were identified from the 13 sequences of C. carinata, with no clear geographic pattern in the haplotype network. The molecular phylogeny thus confirms the widespread distribution of C. carinata across the Indo-West Pacific, facilitated by its migratory hosts.